High Glucose Treatment Limits Drosha Protein Expression and Alters AngiomiR Maturation in Microvascular Primary Endothelial Cells via an Mdm2-dependent Mechanism - Brian Lam; Emmanuel Nwadozi; Tara L. Haas; Olivier Birot; Emilie Roudier (Cells, 2021)
Diabetes promotes an angiostatic phenotype in the microvascular endothelium of skeletal muscle and skin. Angiogenesis-related microRNAs (angiomiRs) regulate angiogenesis through the translational repression of pro- and anti-angiogenic genes. The maturation of micro-RNA (miRs), including angiomiRs, requires the action of DROSHA and DICER proteins. While hyperglycemia modifies the expression of angiomiRs, it is unknown whether high glucose conditions alter the maturation process of angiomiRs in dermal and skeletal muscle microvascular endothelial cells (MECs). Compared to 5 mM of glucose, high glucose condition (30 mM, 6–24 h) decreased DROSHA protein expression, without changing DROSHA mRNA, DICER mRNA, or DICER protein in primary dermal MECs. Despite DROSHA decreasing, high glucose enhanced the maturation and expression of one angiomiR, miR-15a, and downregulated an miR-15a target: Vascular Endothelial Growth Factor-A (VEGF-A). The high glucose condition increased Murine Double Minute-2 (MDM2) expression and MDM2-binding to DROSHA. Inhibition of MDM2 prevented the effects evoked by high glucose on DROSHA protein and miR-15a maturation in dermal MECs. In db/db mice, blood glucose was negatively correlated with the expression of skeletal muscle DROSHA protein, and high glucose decreased DROSHA protein in skeletal muscle MECs. Altogether, our results suggest that high glucose reduces DROSHA protein and enhances the maturation of the angiostatic miR-15a through a mechanism that requires MDM2 activity.